Hubungan Sleep Hygiene dengan Kualitas Tidur pada Mahasiswa Program Studidiploma Tiga Keperawatan Universitas Abulyatama - Cindi Trisa Dela; Urip Pratama; Muhammad Daud (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
College students are often busy completing their assignments. They frequently experience sleep problems that can distort their studies. One of the factors that affects sleep quality is sleep hygiene. Poor sleep hygiene can worsen sleep quality. This study aims to determine the correlation between sleep hygiene and sleep quality among students of the Diploma III Nursing Program at Universitas Abulyatama. This study employs a quantitative correlational-descriptive design applying a cross-sectional approach. The population consisted of 556 students, while the sample was 85 students selected using proportional random sampling. The Sleep Hygiene Index (SHI), with a Cronbach's Alpha of 0.66, measured sleep hygiene. The Pittsburgh Sleep Quality Index (PSQI), with a Cronbach's Alpha of 0.83 of sleep quality. The study took place at Universitas Abulyatama from June 4th to July 3rd, 2025. Bivariate analysis using the chi-square test indicates a significant correlation between sleep hygiene and sleep quality, with a p-value of 0.000 (p ≤ 0.05). The findings reveal that a total of 69.4% of students had good sleep hygiene, and 41.2% had good sleep quality. The results prove that proper sleep hygiene leads to improved sleep quality. Therefore, students should enhance their knowledge on sleep hygiene, as poor sleep hygiene can lead to poor sleep quality.